New fabrication method using additive manufacturing technologies for the pattern of pressed lithium disilicate onlay restorations - Revilla-Leon, Marta; Olea-Vielba, Marina; Esteso-Díaz, Ana; Martinez-Klemm, Iñaki; Reuss Rodriguez-Vilaboa, Jose Manuel; Özcan, Mutlu (Brazilian Dental Science, 2017)
There are 7 categories for the additive manufacturing (AM) technologies and a wide variety of materials that can be used to build a computer aided designed (CAD) 3-Dimensional (3D) object. The present article reviews the main AM processes for polymers for dental applications: stereolithography (SLA), direct light processing (DLP), material jetting (MJ) and material extrusion (ME). The manufacturing process, accuracy and precision of these methods will be reviewed, as well as, their prosthodontic applications. Keywords: 3D printing; Additive manufacturing technologies; Direct light processing; Fused deposition modelling; Material extrusion; Material jetting; Multijet printing; Prosthodontics; Stereolitography.